Strengthening the Digital Literacy of Madrasa Students al-Ittifaqiah Indralaya, South Sumatra - Yanti, Mery; Hapsari Ekonugraheni, Dyah; Mahriani, Retna; Yusnaini, Yusnaini; Effendi, Sofyan (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2024)
Al-Ittifaqiah Islamic Boarding School is an example of a modern Islamic boarding school in Indonesia which adopts limited ICT. In fact, digital literacy is a prerequisite for students to participate in a wider life. Starting from this situation, this service activity aims to improve students' cognitive abilities regarding digital literacy skills. The digital literacy training at Islamic Senior High School of Al-Ittifaqiah Islamic Boarding School involved 46 male and female students. The material presented in a dialogical manner includes the concept of digital literacy, communication ethics in social media, effective communication in the digital era, and motivation to learn in the online learning era. The results of the evaluation indicated that this service was successful in increasing the students' cognitive by 20.93 points. This increase was statistically significant, t (45) = 9.6457, p <0.001. The community service team recommended for the Islamic boarding school to provide internet access for students, at least in the boarding school's computer laboratory. In addition, Sriwijaya University needs to continue to be a boarding school as a service target group because of their uniqueness that combines the traditional education system and the modern education system.